2022
DOI: 10.1037/xlm0001108
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial contiguity are necessary for competition between events.

Abstract: Over the last 50 years, cue competition phenomena have shaped theoretical developments in animal and human learning. However, recent failures to observe competition effects in standard conditioning procedures, as well as the lengthy and ongoing debate surrounding cue competition in the spatial learning literature, have cast doubts on the generality of these phenomena. In the present study, we manipulated temporal contiguity between simultaneously trained predictors and outcomes (Experiments 1–4), and spatial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(62 citation statements)
references
References 125 publications
(196 reference statements)
3
24
2
Order By: Relevance
“…Consistent with Goodyear and Kamil’s findings in Clark’s nutcrackers, tests of landmarks 50 and 70 VU revealed that participants in Group Far (Experiments 1 and 2) showed a better absolute distance estimation than Group Close and slightly better than Group Medium. These results suggest that overshadowing was greater in Group Close, and therefore dependent on goal–landmark spatial proximity, a finding that is by and large consistent with that reported by Herrera and colleagues (Herrera et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with Goodyear and Kamil’s findings in Clark’s nutcrackers, tests of landmarks 50 and 70 VU revealed that participants in Group Far (Experiments 1 and 2) showed a better absolute distance estimation than Group Close and slightly better than Group Medium. These results suggest that overshadowing was greater in Group Close, and therefore dependent on goal–landmark spatial proximity, a finding that is by and large consistent with that reported by Herrera and colleagues (Herrera et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…R. Miller & Matzel, 1988; Pearce & Hall, 1980; Rescorla & Wagner, 1972) have been contrasted. Across humans and other species, competition between features and boundary information has been documented in some reports (e.g., Austen & McGregor, 2014; Herrera et al, 2022) but not in others (Pearce et al, 2001; Redhead & Hamilton, 2007), and hence there is evidence in favor of both families of theories, which has led to numerous debates (e.g., Jeffery, 2010; Pearce, 2009).…”
mentioning
confidence: 99%
“…However, we are not aware of studies exploring whether the signal length is a factor determining overshadowing in humans. In a recent experimental series from our laboratory (Herrera et al, 2022), we did not observe reduced overshadowing with longer CSs; however, this was based on a comparison across experiments, so it should not be considered as conclusive evidence for the absence of an effect of stimulus length in overshadowing.…”
Section: Methodscontrasting
confidence: 63%
“…However, all these studies mentioned above were conducted with nonhuman animals and little evidence is available on the importance of relative salience in human studies. At their best, studies using human participants have identified the specific conditions of temporal and spatial contiguity under which competition or facilitation is more likely to be observed (Alcalá, Kirkden, et al, 2023; Alcalá, Miller, et al, 2023; Glautier, 2002; Herrera et al, 2022). This advises that more research is needed to achieve a better understanding of the specific factors underpinning cue interaction phenomena in human participants.…”
mentioning
confidence: 99%
“…However, a burgeoning question is what variables determine the outcome of the interaction. Urcelay (2017) identified temporal and spatial proximity between events as a relevant factor: across different species and learning domains, contiguity determines whether the interaction between multiple antecedents is competitive or synergistic (Batsell et al, 2012;Cunha et al, 2015;Herrera et al, 2022;Schachtman et al, 1987). Despite the consistency at an empirical level, the aforementioned models are somewhat silent on what effect manipulations of contiguity should have on learning about multiple antecedents.…”
Section: Introductionmentioning
confidence: 99%